Productivity of sawing the machiche wood (Lonchocarpus castilloi Standl), in Tres Garantías, Quintana roo, Mexico - Acosta-Ramos, Alejandra; Martínez-López, Joel (Instituto de Ecología, A.C., 2012)
Yields and sawing time were determined in order to know the sawmilling productivity of Lonchocarpuscastilloi Standl. (machiche). The yields were determined by relating the volume of logs andsawn timber volume of 815 logs. Milling times were determined using the total time method in the mainsaw. Eighty percent of logs recorded diameters from 30 cm to 40 cm, and 94% of them had lengthsfrom 2 m to 3 m. The total volume processed was 194,6 m3 round wood without-bark (rwwb), that generateda volume of 80,8 m3 of sawn lumber. This indicates that to produce one cubic meter of lumber,2,45 m3 of machiche are required. The actual global sawmill coefficient was 41,3%, the coefficient forgrades of boards was 43,1% in boards of sapwood, 34,1% in boards of heartwood, and 22,8% inboards with rejection grade. The productive time was 68%, the non-productive time 19%, and theleisure time 13%. The productivity was at 0,57 m3/ hour. The productivity indicators identified, provideuseful information for the efficient administration for sawmill of the ejido.